Existential Implications of the Concept of Lightness in Milan Kundera's Novel "The Unbearable Lightness of Being" - Amanda, Utriya (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2024)
AbstractThis study aims to investigate the existential implications of the concept of 'lightness' in Milan Kundera's novel "The Unbearable Lightness of Being." The research explores how Kundera's philosophical perspective on 'lightness' contrasts with traditional existential themes of 'heaviness' and historical determinism, as proposed by Nietzsche. Using a qualitative descriptive methodology, the study examines the narrative techniques and character developments in the novel to illustrate Kundera's existential themes. Data were collected through detailed textual analysis of the novel, supplemented by secondary sources such as previous scholarly works, journal articles, and philosophical texts relevant to existentialism. The findings reveal that Kundera uses 'lightness' to depict the freedom from moral and social burdens, highlighting the transient and often absurd nature of human existence. Characters like Tomas and Sabina embody the struggle between 'lightness' and 'heaviness,' reflecting the existential tension between freedom and responsibility. The study concludes that Kundera's narrative encourages readers to contemplate the balance between individual autonomy and the inherent responsibilities of existence, offering a profound critique of the human condition and the quest for meaning in an unpredictable world.AbstrakPenelitian ini bertujuan untuk menyelidiki implikasi eksistensial dari konsep 'lightness' dalam novel Milan Kundera "The Unbearable Lightness of Being." Penelitian ini mengeksplorasi bagaimana perspektif filosofis Kundera tentang 'lightness' bertentangan dengan tema eksistensial tradisional 'heaviness' dan determinisme sejarah, seperti yang diusulkan oleh Nietzsche. Menggunakan metodologi deskriptif kualitatif, penelitian ini memeriksa teknik naratif dan pengembangan karakter dalam novel untuk menggambarkan tema eksistensial Kundera. Data dikumpulkan melalui analisis tekstual mendetail dari novel, ditambah dengan sumber sekunder seperti karya ilmiah sebelumnya, artikel jurnal, dan teks filosofis yang relevan dengan eksistensialisme. Temuan mengungkapkan bahwa Kundera menggunakan 'lightness' untuk menggambarkan kebebasan dari beban moral dan sosial, menyoroti sifat eksistensi manusia yang sementara dan seringkali absurd. Karakter seperti Tomas dan Sabina mewakili perjuangan antara 'lightness' dan 'heaviness,' mencerminkan ketegangan eksistensial antara kebebasan dan tanggung jawab. Penelitian ini menyimpulkan bahwa narasi Kundera mendorong pembaca untuk merenungkan keseimbangan antara otonomi individu dan tanggung jawab inheren dari keberadaan, menawarkan kritik mendalam terhadap kondisi manusia dan pencarian makna dalam dunia yang tidak terduga.Â Â